Does the Beige Book move financial markets? - Madeline Zavodny; Donna K. Ginther (Federal Reserve Bank of Atlanta, 2003)
About two weeks prior to each FOMC meeting, the Federal Reserve releases a description of economic activity in a document called the Beige Book. The authors examine whether the descriptive content of the Beige Book affects asset prices. The results indicate that more positive Beige Book reports on economic growth are associated with increases in interest rates, particularly long-term rates, even after controlling for other macroeconomic data releases. Stronger Beige Book reports are positively associated with changes in equity prices during expansions but negatively during recessions.
Keywords: 330; Business forecasting; Economic conditions - United States; Federal Reserve System; Economic indicators; Financial markets